2009
DOI: 10.1016/j.jhazmat.2008.12.130
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and physiology of anaerobic granular sludge exposed to an organic solvent

Abstract: The use of quantitative image analysis techniques, together with physiological information might be used to monitor and detect operational problems in advance to reactor performance failure. Industrial organic solvents, such as White Spirit, are potentially harmful to granular sludge. In preliminary batch assays, 33 mg L(-1) of solvent caused 50% relative biomass activity loss. In an expanded granular sludge blanket reactor fed with 40 mg L(-1) of solvent, during 222h, the reactor performance seemed to be unaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Although QIA techniques have already been successfully applied to monitor anaerobic granular sludge [29][30][31], to the authors' knowledge, studies regarding the application of QIA to AGS systems are still scarce. Nonetheless, the application of QIA can be a useful tool to characterize, for example, the start-up of AGS systems and the structure of mature AGS, as well as to monitor the balance between suspended and granular fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Although QIA techniques have already been successfully applied to monitor anaerobic granular sludge [29][30][31], to the authors' knowledge, studies regarding the application of QIA to AGS systems are still scarce. Nonetheless, the application of QIA can be a useful tool to characterize, for example, the start-up of AGS systems and the structure of mature AGS, as well as to monitor the balance between suspended and granular fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, no significant size reduction of anaerobic granules in an EGSB reactor could be observed in the larger aggregates in the case of two groups after detergent shocks [9]. Moreover, it was found that anaerobic granules experienced fragmentation, and about 50% loss of specific acetoclastic activity occurred suffering 33 mg/L of solvent, while the overall reactor performance was unaffected by a White Spirit shock load of 9 days at 40 mg/L [10]. To accurately predict the overall performance of the anaerobic granules in the presence of environment fluctuations, integration of morphological and physiological changes might be indispensable.…”
Section: Introductionmentioning
confidence: 91%
“…In a different experiment, a commercial detergent and a solvent were fed to lab-scale expanded granular sludge bed (EGSB) reactors to detect the effects of toxic compounds from the cleaning stages (Costa et al 2007(Costa et al , 2009b. The inhibitory effects were dependent on the surfactant concentration and exposure time.…”
Section: Toxic Eventsmentioning
confidence: 99%
“…Furthermore, the LfA parameter acted as an early-warning indicator of the biomass washout, since it increased 3 and 5 days before effluent VSS increase, respectively, in shock with 150 and 300 mg COD L −1 of detergent (Costa et al 2007). During the solvent shock load (Costa et al 2009b), the percentage of the aggregates projected area with D eq >1 mm decreased from 81 to 53 %. Furthermore, the mean D eq of the aggregates >0.2 mm decreased, as well as the settling velocity, showing that the granules underwent a fragmentation process (Fig.…”
Section: Toxic Eventsmentioning
confidence: 99%
See 1 more Smart Citation